Forensic Phonetics: definition and main areas of application - San Segundo Fernández, Eugenia (Círculo de Lingüística Aplicada a la Comunicación, 2023)
This work critically reviews the field of applied linguistics known as Forensic Phonetics. From the very name of this discipline we find some terminological controversies, not only concerning how to refer to this branch of knowledge, but also concerning what are –and how to name– its main areas of application. Thanks to a detailed literature review, we describe the five major fields of Forensic Phonetics, with an emphasis in demystifying possible misconceptions about the scope of this discipline. Likewise, an effort has been made to present the results of the most recent research, especially in the field of forensic speaker comparison, which is the best known task in Forensic Phonetics. For this reason, more space is devoted to this sub-area, focusing on current methodological approaches, as well as on the most used phonetic parameters.
Keywords: areas of application; forensic phonetics; forensic speaker comparison